Hubungan Sekolah dengan Masyarakat di Sd Negeri No. 195/Vi Pematang Kancil - Dandi Kurniawan; Vina Sulistia; Yantoro Yantoro; Bradley Setiyadi (Sahabat Publikasi, 2023)
The objective of this study was to describe the relationship between the school and community planning, to determine the implementation of school and community relations , to know the principals evaluate the implementation of school and community relations. This research is a qualitative descriptive study. The subject of this research is principal, teachers, students, and parents committee chairman. Data collection techniques are observation, interviews , and documentation. Data analysis techniques is data collection, data reduction, data presentation, and conclusion. After the study concluded that the relationship of the school with the community goes well.